Vitellogenin, juvenile hormone, insulin signaling, and queen honey bee longevity - Corona, Miguel; Velarde, Rodrigo A; Remolina, Silvia; Moran-Lauter, Adrienne; Wang, Ying; Hughes, Kimberly A; Robinson, Gene E (Proceedings of the National Academy of Sciences - PNAS, 2007)
In most animals, longevity is achieved at the expense of fertility, but queen honey bees do not show this tradeoff. Queens are both long-lived and fertile, whereas workers, derived from the same genome, are both relatively short-lived and normally sterile. It has been suggested, on the basis of results from workers, that vitellogenin (Vg), best known as a yolk protein synthesized in the abdominal fat body, acts as an antioxidant to promote longevity in queen bees. We explored this hypothesis, as well as related roles of insulin-IGF-1 signaling and juvenile hormone. Vg was expressed in thorax and head fat body cells in an age-dependent manner, with old queens showing much higher expression than workers. In contrast, Vg expression in worker head was much lower. Queens also were more resistant to oxidative stress than workers. These results support the hypothesis that caste-specific differences in Vg expression are involved in queen longevity. Consistent with predictions from Drosophila, old queens had lower head expression of insulin-like peptide and its putative receptors than did old workers. Juvenile hormone affected the expression of Vg and insulin-IGF-1 signaling genes in opposite directions. These results suggest that conserved and species-specific mechanisms interact to regulate queen bee longevity without sacrificing fecundity.